2012
DOI: 10.1530/joe-12-0055
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of exogenous [125I]-3-iodothyronamine in mouse in vivo: relationship with trace amine-associated receptors

Abstract: 3-Iodothyronamine (T 1 AM) is a novel chemical messenger, structurally related to thyroid hormone, able to interact with G protein-coupled receptors known as trace amine-associated receptors (TAARs). Little is known about the physiological role of T 1 AM. In this prospective, we synthesized 125 I]-T 1 AM was taken up by each organ. A significant increase in tissue vs blood concentration occurred in gallbladder, stomach, intestine, liver, and kidney. Tissue radioactivity decreased exponentially over time, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 29 publications
3
60
1
1
Order By: Relevance
“…Subsequently, additional molecular targets were tentatively identified, including alpha-2 receptors (Regard et al, 2007). Whether the behavioral effects of T1AM result from the activation of such receptors remains to be demonstrated (Chiellini et al, 2012;Panas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, additional molecular targets were tentatively identified, including alpha-2 receptors (Regard et al, 2007). Whether the behavioral effects of T1AM result from the activation of such receptors remains to be demonstrated (Chiellini et al, 2012;Panas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that TAAR, or at least TAAR1, agonist activation is not necessary for at least some of the metabolic responses due to T1AM. Radioactive tracing of exogenous 125 I labeled-T1AM did not indicate any direct relationship with TAAR receptor expression across 8 different TAAR isoforms and measured radioactivity in tissues [23]. Additionally, it was found that expression of TAARs in mice and rat proved to be very low in most tissues; TAAR gene expression was only detected in trace amounts across most tissues, with notable expression levels of TAAR1 in the stomach and testis, and TAAR8 in the testis, intestine, and spleen [23].…”
Section: T1am Mechanism Of Action Through Transmembrane Spanning G-prmentioning
confidence: 88%
“…Distribution of measured radioactivity in response to acute 125 I labeled-T1AM injection in mice indicated abundant levels of accumulation in stomach, intestine, kidney, and gallbladder within as little as 30 minutes [23]; however, this is thought to reflect excretion pattern of excess T1AM rather than functional activity sites. Elevated radiation levels in liver, fat, and skeletal muscle for a full 24 hours after 125 I labeled-T1AM injection provides evidence for these tissues as possible storage sites of T1AM [23].…”
Section: Distribution and Transportmentioning
confidence: 98%
See 2 more Smart Citations